PENGARUH KUALITAS LAYANAN TERHADAP PELANGGAN DI A&W RESTAURANT INDONESIA - Asep Parantika; Devina Nisa Liora (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
The quality service expected by consumers is good facilities and service, comfort, safety, tranquility, and satisfactory results. The purpose of this study is to find out whether there is an influence of service on customer satisfaction, how much service contributes to customer satisfaction of A & W Restaurant. This research was conducted using qualitative descriptive using a case study approach that has service quality variables as independent variables and customer satisfaction on bound variables. This research was conducted by interviews and observations. The results of the study show that the staff of A&W Restaurant have implemented five dimensions of service quality, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy, so that guests still remain loyal, even though there are still many things to be improved.